Rabies vaccination induces a CD4+ TEM and CD4+CD8+ TEMRA TH1 phenotype in dogs. - Haeree P Lang; Farah F Almeer; Marc K Jenkins; Steven G Friedenberg (PLoS ONE, 2025)
The canine rabies vaccine consists of the whole killed rabies virus and an alum adjuvant. While it is known to provide immunological protection in dogs, its effects on cell-mediated responses remain largely uncharacterized. Here, we analyzed blood and spleen samples from vaccinated dogs to understand adaptive immune responses ex vivo following restimulation with rabies vaccine antigens. Our results showed that recombinant rabies virus glycoprotein (RABV-G) elicited higher antibody titers and IFNγ production compared to recombinant rabies virus nucleoprotein (RABV-N). CD4+ and CD4+CD8+ double-positive (DP) T cells proliferate robustly after five days of RABV-G stimulation, which was inhibited by an anti-canine MHC class II blocking antibody. Both RABV-G-specific CD4+ and DP T cells demonstrated a polarized TH1 phenotype, with minor subsets showing TH1/TH17 hybrid and pathogenic TH1/TH17 hybrid cell features. CD4+ T cells were primarily effector memory T cells (TEM), while DP T cells exhibited a terminally differentiated effector memory phenotype that re-expressed CD45RA (TEMRA). Both RABV-G-specific CD4+ and DP T cells were detectable up to 1,024 days post-vaccination in spleen samples and their proliferative capacities were unaffected by age. Our results provide the first characterization of canine RABV-G-specific T cell phenotypes in the spleen and blood following rabies vaccination.